2016
DOI: 10.1098/rsob.160153
|View full text |Cite
|
Sign up to set email alerts
|

Tale of a multifaceted co-activator, hADA3: from embryogenesis to cancer and beyond

Abstract: Human ADA3, the evolutionarily conserved transcriptional co-activator, remains the unified part of multiple cellular functions, including regulation of nuclear receptor functions, cell proliferation, apoptosis, senescence, chromatin remodelling, genomic stability and chromosomal maintenance. The past decade has witnessed exciting findings leading to considerable expansion in research related to the biology and regulation of hADA3. Embryonic lethality in homozygous knockout Ada3 mouse signifies the importance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The variant was present in all seven affected individuals in the three-generation pedigree, but also present as a heterozygous variant in the unaffected grandfather. This gene is a component of the histone acetyl transferase (HAT) coactivator complex and a regulator of p53 and it is important for chromatin modulation and cell cycle progression 47 . TADA3 is universally highly expressed in brain regions (> 70 TPM in the GTEx data) 30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variant was present in all seven affected individuals in the three-generation pedigree, but also present as a heterozygous variant in the unaffected grandfather. This gene is a component of the histone acetyl transferase (HAT) coactivator complex and a regulator of p53 and it is important for chromatin modulation and cell cycle progression 47 . TADA3 is universally highly expressed in brain regions (> 70 TPM in the GTEx data) 30 .…”
Section: Resultsmentioning
confidence: 99%
“…TADA3 is universally highly expressed in brain regions (> 70 TPM in the GTEx data) 30 . As a multifaceted protein, TADA3 plays an important role in chromatin remodeling, cellular proliferation, cellular senescence, DNA damage response, and embryonic development 47 .…”
Section: Resultsmentioning
confidence: 99%
“…ADA3 has been shown to interact with other various proteins associated with tumorigenesis, including HPV16 E6 protein [27,28] and p53 [29,30]. Additionally, a number of previous studies have identified alterations in ADA3 as contributing factors in diverse cancer types [31]. However, to the best of the authors' knowledge, relatively few studies have investigated the potential contribution of TADA3 to NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“… 370 Mirza et al 371 have reported that ADA3 is over expressed in breast cancer patients and as a transcriptional co-activator, human ADA3 (hADA3) interacts with ERα, thereby transactivating its downstream targets leading to breast cancer progression. 372 …”
Section: Diseases Associated With Mutation Of Transcription Co-activa...mentioning
confidence: 99%